AUDIT AT SCHOOL: BETWEEN PROCESS AND STRATEGY - Prakapas, Romas; Targamadzë, Vilija (Acta Paedagogica Vilnensia, 2008)
Based on the retrospective analysis, that was done back in 2007 in November–December, the results of external evaluators of school management and educational activity are given in this paper. The aim of this research is to present the processes of internal audit at school and to reveal its influence for the further planning. Analyzed problems were put in such questions: how the audit process is going on in real within school activity?; what influence the internal audit’s procedure makes for the school activity’s effectiveness and strategic planning? While pointingout the peculiarites of the phenomenon of auditing, it was not based on the positive comprehensive schools’ internal audit’s experience, which is stated widely in various project reports and other scientific articles. On the contrary, it was mostuly orientated towards expressing main problems in order to raise educational discussions. The object of this research is the reports of external evaluators on school management and educational activity. The aim of the research is to reveal the processes of internal school audit and its influence for further planning. Some conclusions were made such as that negative influence on school’s internal audit is done by directive and controlled ruling of the institution that is based on vertical interactions, lack of strategic thinking, and formalizing the qualitative educational processes.